Can children use probability to guide their choices under uncertainty? - Lu, Julianna (University of Waterloo, 2022)
We encounter situations in our everyday lives where we need to make decisions under uncertainty. But what kind of information do we use and what abilities are helpful to us when making decisions under uncertainty? In three experiments (Total N = 180), I examined whether 3- to 7-year-olds could use numerical information (e.g., probability) to judge which of two situations presented with more or less uncertainty. Children were shown two games with different numbers of hiding locations. Using a within-subjects design, they were asked to select the game that would make it either easy or hard for someone else to find a coin that is hidden under one of the locations. Around the age of five, children selected the side with fewer hiding locations when asked to make it easy to find the coin and selected the side with more hiding locations when asked to make it hard to find the coin (Experiment 1). Findings from Experiment 2 suggest that children do this by considering the absolute number of hiding locations, rather than using perceptual cues like surface area (e.g., clutter). In Experiment 3, we simplified our procedure to examine whether younger children could make a similar inference. Findings reveal that even 4-year-olds were selecting the side with fewer hiding locations when asked which ball was easier to find and selecting the side with more hiding locations when asked which ball was harder to find. These results suggest that around age four, children can evaluate probability to make judgements about levels of uncertainty. Moreover, these results highlight that perhaps evaluating the probabilities of outcomes is a helpful tool when confronted with uncertainty.
Keywords: numerical reasoning; probability; cognitive development; decision-making